2010
DOI: 10.1108/jopp-10-01-2010-b003
|View full text |Cite
|
Sign up to set email alerts
|

Social cohesion, groupthink and ethical behavior of public procurement officers

Abstract: Whereas social cohesion has been widely studied and researched by sociologist and psychologists, its application to public procurement is sparse. This study explores the connection between social cohesion, groupthink, ethical attitudes and ethical behavior of procurement officers. The study is based on a survey of 405 public procurement officers in central government. A cross-sectional survey design was used and a response rate of 58.5% attained. Self report items were used to study all the constructs. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It is therefore imperative that governments pay particular attention to public procurement in order to create wealth for the growth and development of their economies (Munyera, 2014). In fact, huge sums of tax payers' money get wasted due to inefficient and ineffective procurement structures, poor monitoring systems, non adherence to policies and procedures, non-compliance to regulations as well as the failure of authorities to impose and implement sanctions for violations of procurement rules (Ntayi et al, 2010a). In order to improve the management of public procurement, many countries have come up with procurement reforms.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative that governments pay particular attention to public procurement in order to create wealth for the growth and development of their economies (Munyera, 2014). In fact, huge sums of tax payers' money get wasted due to inefficient and ineffective procurement structures, poor monitoring systems, non adherence to policies and procedures, non-compliance to regulations as well as the failure of authorities to impose and implement sanctions for violations of procurement rules (Ntayi et al, 2010a). In order to improve the management of public procurement, many countries have come up with procurement reforms.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with Banwo et al (2015), Chang and Bordia (2001), Mullen et al (1994) and Rose (2011), who found out that the relationship between group cohesion and good or poor performance of a group is complicated. This suggests that attention in our context may need to shift away from cohesiveness of groups to other factors when groupthink behaviour is to be avoided as also indicated by other studies (t ' Hart, 1991;Mpeera Ntayi et al, 2010).…”
Section: Groupthink and Decision Makingmentioning
confidence: 60%
“…The groupthink predictors studied in this study were cohesiveness, trust, conformity, promotional leadership and members' diversity as adopted from different researchers (Baptist, 2015;Janis, 1991;Park, 2000). On assessing the presence of each predictor, statements were developed on the basis of different kinds of literature as follows: Group cohesiveness (Banwo et al, 2015;Mpeera Ntayi et al, 2010;Mullen et al, 1994;Park, 2000;Turner et al, 1992); Trust (Simons and Peterson, 1998;Janis, 1991;t' Hart, 1991;Baptist, 2015). Leadership styles in groups was also assessed to identify the presence of promotional leadership which has been mentioned as a profound antecedent from (Rose, 2011) and Group members diversity adopted from Baptist (2015), Park (2000), Smith and Nichols (2015).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Based on the literature, tendering performance is influenced by rigid procurement legislation that focuses on open competition and a price-centric approach with narrow specifications (Harland et al , 2013; Uyarra et al , 2014). This creates unfavourable collective norms and excessive compliance to regulations, distorting individual creativity and rational decisions (Mpeera Ntayi et al , 2010). For instance, public buyers may partially select unqualified or lower-bid suppliers because of existing norms that reinforce efficiency over effective tendering (Dekel and Dotan, 2018; Dekel and Schurr, 2014).…”
Section: Antecedents and Contingencies And Their Effect On Performancementioning
confidence: 99%